Insomnia: definition, pathophysiological models, diagnosis, and treatment - Sakalauskaitė-Juodeikienė, E.; Masaitienė , R. (Neurologijos seminarai, 2018)
Insomnia is defined as a disorder, characterized by recurrent difficulties initiating and maintaining sleep or waking up earlier than desired, associated with daytime symptoms which occur at least three times per week and are present for at least 3 months when the symptoms can not be explained by inadequate opportunities or poor circumstances for sleep or by an other sleep disorder. Diagnostic procedure for insomnia should include evaluation of sleep–wake behaviour and sleep history, as well as questions about somatic and mental disorders, anamnesis of medication and other substances used, physical examination, sleep questionnaires and sleep diaries, and additional measures. Sleep diaries or actigraphy can be used to evaluate sleep–wake schedules or circadian rhythm disorders. Polysomnography is recommended when other sleep disorders (periodic limb movement disorder, sleep apnea or narcolepsy) are suspected, also for treatment-resistant insomnia. Cognitive behavioural therapy is recommended as the first-line treatment for chronic insomnia in adults of any age. A pharmacological intervention can be offered if cognitive behavioural therapy is not effective or not available. Benzodiazepines and benzodiazepine receptor agonists are effective for short-term treatment of insomnia. Long-term treatment of insomnia with benzodiazepines and benzodiazepine receptor agonists is not recommended. Sedating antidepressants are effective for short-term insomnia treatment. Antihistaminics and antipsychotics are not recommended for insomnia treatment because of insufficient evidence. Melatonin is not recommended for the treatment of insomnia because of low efficacy. Phytotherapeutics are not recommended for the treatment of insomnia because of poor evidence. Light therapy and exercise regimes may be useful as adjunct therapies. Acupuncture, aromatherapy, foot reflexology, homeopathy, meditative movement, moxibustion, and yoga are not recommended for the treatment of insomnia because of poor evidence.